Multi-stakeholder Platform: An innovative mechanism for promoting integrated decision making in the Stung Pursat catchment - Ministry of Water Resources and Meteorology, Cambodia; Supreme National Economic Council, Cambodia; Tonle Sap Authority; Culture and Environment Preservation Association; Hatfield Consultants (2013)
Introduced as an innovation in the Stung Pursat catchment of Cambodia, a MSP was piloted to promote integrated water resource management (IWRM). The “Fostering-Evidence-based IWRM in Stung Pursat catchment, Cambodia project1 (MK 16)” supported three MSP sessions in Pursat, and brought-together over 40 participants from government (national, provincial, and municipal), civil society organizations (including academic institutions), and community-based natural resource communities.